Secondary Students’ Sensory Preferences and Their Influence on Science Academic Achievement - Ortega-Torres, E.; Solaz-Portolés, J. J.; Sanjosé-López, V. (Jurnal Pendidikan IPA Indonesia, 2021)
Evidence has been found that some students seem to have learning obstacles associated with particular sensory preferences when dealing with instructional materials. Therefore, knowing students’ sensory preferences could help teachers improve instructional resources. Our objectives were: (1) to describe Secondary students’ sensory preferences according to gender and age; (2) to analyse the possible association between students’ sensory preferences and their general academic achievement in science. We conducted a synchronic, cross-sectional descriptive study in a sample of 582 male and female students from 7th to 11th grade using the VARK questionnaire. There was a significant predominance of sensory preferences containing the Kinesthetic mode, and the preferences containing the Visual mode were the least frequent. Girls or boys showed similar distributions of sensory preferences. Using linear regression to predict students’ general academic achievement from VARK scores, we obtained a significant contribution of the Kinesthetic score, and a minor but still significant single contribution of the Reading/Writing score.